Luxury Tourism in South Africa: navigating opportunities and barriers to address sustainability challenges - Chasenski, Daniella (Graduate School of Business (GSB), 2025)
The global luxury tourism industry is increasingly challenged to balance growth and sustainability, particularly in developing regions such as South Africa. This study explores the opportunities and challenges faced by luxury tourism businesses in integrating sustainability into their operations. Focusing on three luxury game lodges in the Sabi Sands Game Reserve, this research analyses how these businesses navigate the tensions between environmental conservation, socio-cultural impact, and economic viability. Key research questions include: How do they navigate sustainability challenges within their unique contexts? What are they currently doing, and what more can they do? How can luxury tourism businesses improve their sustainability practices? This study adopts an exploratory, qualitative research approach, using a multiple-case study design. Data was collected through nine semi-structured interviews with heads of environment and sustainability, lodge managers and game rangers, alongside document analysis, to examine sustainability strategies and their implementation across the selected lodges. Findings reveal that while lodges have implemented sustainability initiatives, they continue to face systemic barriers such as guest expectations, financial constraints, infrastructure limitations, and reliance on international tourism. However, innovative solutions, including community-driven conservation, local economic integration, and sustainable business models, demonstrate how luxury and sustainability can coexist. This research contributes empirical insight to a limited body of literature on sustainability in South African luxury tourism. It provides practical recommendations for industry stakeholders and policymakers, such as addressing neocolonial ownership structures, developing standardised impact assessment models, aligning sustainability with guest expectations, and leveraging public-private partnerships to scale green technologies. Future research should adopt a mixed-methods approach to quantify long-term sustainability impacts, guest perceptions, and policy effectiveness, strengthening the evidence base for a more equitable and resilient luxury tourism sector.